2014
DOI: 10.3389/fphys.2014.00172
|View full text |Cite
|
Sign up to set email alerts
|

Roles of gap junctions, connexins, and pannexins in epilepsy

Abstract: Enhanced gap junctional communication (GJC) between neurons is considered a major factor underlying the neuronal synchrony driving seizure activity. In addition, the hippocampal sharp wave ripple complexes, associated with learning and seizures, are diminished by GJC blocking agents. Although gap junctional blocking drugs inhibit experimental seizures, they all have other non-specific actions. Besides interneuronal GJC between dendrites, inter-axonal and inter-glial GJC is also considered important for seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 151 publications
0
86
0
1
Order By: Relevance
“…The gap junctions of the astrocytes were also found to affect the hyperexcitability of the system. This has been demonstrated in studies of cerebral tissue from animal seizure models and human patients, where there was an up-regulation of glial gap junctional mRNA and protein [128].…”
Section: Glial Cells Play An Important Role In Hyperexcitabilitymentioning
confidence: 80%
“…The gap junctions of the astrocytes were also found to affect the hyperexcitability of the system. This has been demonstrated in studies of cerebral tissue from animal seizure models and human patients, where there was an up-regulation of glial gap junctional mRNA and protein [128].…”
Section: Glial Cells Play An Important Role In Hyperexcitabilitymentioning
confidence: 80%
“…Changes in expression levels and/or channel function formed by several different Cxs have been associated with a number of central nervous system (CNS) disorders. Among these, we can mention X-linked Charcot-Marie-Tooth disease (Bergoffen et al, 1993), traumatic injury of the brain and/or spinal cord (Cronin et al, 2008), hypersynchronous neuronal activity associated with seizures (Seifert et al, 2010; Mylvaganam et al, 2014), and several others (Retamal et al, 2015; Xie et al, 2015). Treatment with a mimetic peptide reduces tissue damage by downregulating gliosis and cytokine release (O'Carroll et al, 2013).…”
Section: Modulation Of Connexins By Mirnasmentioning
confidence: 99%
“…PANX1 in the hippocampus has also been associated with murine models of epilepsy. Studies have shown that PANX1 levels are increased in epilepsy, and that the N-methyl-D-aspartate receptor can activate the opening of PANX1 channels, thereby raising extracellular ATP [39] and arachidonic acid levels, and promoting epileptiform activity [19,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%